2021
DOI: 10.3390/app11125622
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Corrosion Resistance of TiAl6V4 Alloy Produced with SLM Technique and Used for Customized Mesh in Bone Augmentations

Abstract: Bone augmentation procedures represent a real clinical challenge. One option is the use of titanium meshes. Additive manufacturing techniques can provide custom-made devices in titanium alloy. The purpose of this study was to investigate the material used, which can influence the outcomes of the bone augmentation procedure. Specific test samples were obtained from two different manufacturers with two different shapes: surfaces without perforations and with calibrated perforations. Three-point bending tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The existing evidence does not report whether the part exposed to the oral cavity and, thus, to contaminants such as food and beverages but also to sudden and extremely variable chemical conditions, may influence or not the surface of the device, affecting the bone response. In a previous study [14] the analysis revealed the presence of external and internal defects after the exposure to acid solutions, but it was expected that on human devices like those examined in this study, the findings would have been different, especially because the exposure to the oral cavity is less aggressive than a pH 4 laboratory solution.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The existing evidence does not report whether the part exposed to the oral cavity and, thus, to contaminants such as food and beverages but also to sudden and extremely variable chemical conditions, may influence or not the surface of the device, affecting the bone response. In a previous study [14] the analysis revealed the presence of external and internal defects after the exposure to acid solutions, but it was expected that on human devices like those examined in this study, the findings would have been different, especially because the exposure to the oral cavity is less aggressive than a pH 4 laboratory solution.…”
Section: Discussionmentioning
confidence: 61%
“…In a more recent article published [14], TiAl6V4 samples fabricated by two different manufacturers (BTK Vicenza, Italy and Bone Easy Lisboa, Portugal) were experimentally compared after being dipped into buffered solutions for 7, 14 and 21 days at different pH (4 and 7) in order to artificially simulate the oral exposure. The effect of the acid solution, although not reproducible in humans, revealed that both samples were extremely resistant, but the surface showed a moderate degree of corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, meshes obtained through 3D printing have several surgical advantages, including higher precision without the need for intra-surgical adaptation, plasticity and space-making, and round margins and corners. However, the high costs associated with this printing technique and the materials it employs may represent important limitations [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Techniques involve placing a mechanical barrier to protect the blood clot and to isolate the bony defect from the surrounding connective and epithelial tissue invasion. This space is needed to allow the osteoblasts to access the space intended for bone regeneration [5,6].…”
Section: Introductionmentioning
confidence: 99%